The impact of macroeconomic variables towards unemployment rate: A study on Malaysia and Singapore from the year 1986-2006 / Sahida Abdul Satar - Abdul Satar, Sahida (2007)
This study aim to examine the impact of macroeconomic variables on unemployment rate in Malaysia and Singapore. This studies will examine how macroeconomic variables such as GDP, FDI, and population (growth rate) will give effect to unemployment rate in both country. This studies involved by comparing the different level of unemployment rate in Malaysia and Singapore that are influence by these macroeconomic variables. For this purpose a Multiple Linear Regression Model and Anova will be used. This study includes data from the year 1986 - 2006. Based on the analysis, it show that FDI has a significant effect towards unemployment rate in Malaysia while other two macroeconomic variables such as GDP and Population has no significance effect towards overall unemployment rate in Malaysia. The result also showed that GDP and FDI has a significance effect towards unemployment rate in Singapore.